A critical analysis of the English Proficiency Index (EPI) 2020 from the view of high school English teachers. - Márquez Andrade, Karen Alejandra (2022)
The research project “A critical analysis of the English Proficiency Index (EPI) 2020 from the view of high school English teachers” was developed with the main objective of analyzing the results of the Standard English Test presented in the English Proficiency Index 2020 from the view of English teachers from Unidad Educativa Riobamba. This research presents a qualitative approach and a descriptive-explanatory level. Additionally, interview guides and surveys were designed so as to collect the necessary data from the population, which was formed by 14 English teachers from the selected institution alongside a representative of the Education First program. The mentioned instruments aimed to identify the factors that influence the English level of Ecuador and the view of the teachers regarding the reliability of the results from the EPI 2020. The obtained results indicate factors such as education investment, educational policies, curricular guidelines, and the English teachers’ training and methodology are the main factors that influenced the level of English in our country. Furthermore, the results from the EPI 2020 are considered a reliable reference for the English level in our country. However, the creation of a contextualized test that measures language proficiency while considering the Ecuadorian context is a proposal well received by most of these educators.